Molecular gene cloning and sequencing of glutamate decarboxylase gene from Lactobacillus delbrueckii and Lactobacillus reuteri - Taherzadeh, Mahsa; Esmaeili, Abolghasem; Rabbani, Mohammad (Archives of Advances in Biosciences, 2015)
Glutamate decarboxylase enzyme produces γ-aminobutyric acid (GABA) in a non-reversible decarboxylation reaction of glutamate. GABA is a major inhibitory neurotransmitter of the brain and it is also present at high concentration in other organs such as pancreatic islets. GABA has effects on blood pressure, diabetes, inflammation, sleeplessness and depression. Some bacteria such as Lactobacillus strains are capable of GABA production. Identification of these bacteria is important both for researchers and industry. The aim of this study was molecular gene cloning and sequencing of glutamate decarboxylase (gad) from Lactobacillus delbrueckii subsp. bulgaricus ATCC 11842 and Lactobacillus reuteri ATCC 23272. These strains were cultured in MRS medium at 37○C for 24 hours. For cloning gad gene from these strains, polymerase chain reaction (PCR) was performed using specific primers designed by Oligo7 software. PCR production was extracted from agarose gel and was inserted into PGEM-T vector using T4 DNA ligase enzyme and then it was transformed to E. coli XL1Blue. In the final step, white colonies were selected and after plasmid extraction, the existence of gad gene in recombinants was confirmed by PCR. Gad gene was cloned from Lactobacillus delbrueckii subsp. bulgaricus ATCC 11842 and Lactobacillus reuteri ATCC 23272. It is for the first time that the gad gene sequences from these bacteria were registered on NCBI with accession numbers KF751355 and KF751352 respectively. The result of this research indicates that the two aforementioned bacteria contain glutamate decarboxylase gene and therefore they possibly can be used for industrial γ-aminobutyric acid production.